2015
DOI: 10.3109/08820139.2015.1017046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunomodulatory Effects of Mesenchymal Stem Cells Soluble Factors on miR-155 and miR-23b Expression in Mice Dendritic Cells

Abstract: Mesenchymal stem cells (MSCs) can modulate dendritic cells (DCs) activation and induce tolerogenic characteristics in DCs. All mechanisms involved in MSCs-induced tolerogenic DCs are not fully understood. MicroRNAs (miRs) play important role in maturation and function of DCs. In this study, we investigated the effects of MSCs culture supernatant (C.S.) on expression of miR-155 and miR-23b in mice DCs. BALB/c mice spleens were used for DCs isolation. MSCs were isolated from the mice bone marrow and cultured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Moreover, it was observed that mir-126, PG2 treatment had no significant effect on mir-23 expression compared to the control group. In this line, Wu et al (2017) showed that miR-23b overexpression inhibited activation of the NF-jB pathway, so mir-23 may have a positive regulatory effect on the immunoregulatory property of MSCs (Karachi et al, 2015, Wu et al, 2017. According to our results, it can be expected that the upregulation of mir-23 by PGEs treatment can improve the immunoregulatory properties of Ad-MSCs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Moreover, it was observed that mir-126, PG2 treatment had no significant effect on mir-23 expression compared to the control group. In this line, Wu et al (2017) showed that miR-23b overexpression inhibited activation of the NF-jB pathway, so mir-23 may have a positive regulatory effect on the immunoregulatory property of MSCs (Karachi et al, 2015, Wu et al, 2017. According to our results, it can be expected that the upregulation of mir-23 by PGEs treatment can improve the immunoregulatory properties of Ad-MSCs.…”
Section: Discussionsupporting
confidence: 54%
“…MSCs have gained extensive recognition and international attention because of their immunomodulatory properties and use of this capacity for the treatment of autoimmune and degenerative diseases (Kuo et al, 2012, Willis et al, 2018. In addition, miRNAs can influence the immune-regulatory activities of MSCs through targeting various modulatory genes, as a positive regulator or negative regulator (Xu et al, 2013;Karachi et al, 2015;Wu et al, 2015;Khosravi et al, 2017;Onodera et al, 2017;Wu et al, 2017) In addition, studies have shown that PG has different properties such as anti-inflammatory effects by modulating some miRNAs expression and this target gene, which plays a role in the inflammatory pathway (Banerjee et al, 2012(Banerjee et al, , 2013. So, in this study, we assess the impact of PGEs on immunoregulatory-related miRNAs expression in Ad-MSCs for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic GVAX vaccine has been studied for treatment of prostate cancer [42] [49]. DCs act as a double-edged sword that can induce both immune tolerance and immune activation depending on which receptors on DCs are engaged [50]. Maturation and migration of DCs play a critical role in characteristics of DCs [51].…”
Section: Cancer Vaccinesmentioning
confidence: 99%
“…Mesenchymal stem cells soluble factors could modulate some speci c miRs expression, like those of miR-155 and miR-23b in dendritic cells (23). Whether miRs are involved in underlying mechanism of CD4 + T cells in response to MSCs upon hypoxic and in ammatory condition during ARDS needs further investigation.…”
mentioning
confidence: 99%